2013
DOI: 10.4254/wjh.v5.i7.393
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotypes in north eastern Algeria: A retrospective study

Abstract: AIM:To determine the frequency of various hepatitis C virus (HCV) genotypes present in patients from north eastern Algeria. METHODS:This is a retrospective cross-sectional study of 435 HCV infected patients from northeast Algeria, detected in the Sadelaoud laboratory and diagnosed between January 2010 and December 2012. The patients were diagnosed with HCV infection in their local hospitals and referred to be assessed for HCV genotype before the antiviral treatment. Demographic information (sex, age and addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
3
14
1
Order By: Relevance
“…Interestingly, it was observed that the predominant genotypes in males were 1b, 1c, 3a, 3b, 5a and 6a versus 1a, 2a, 2b and 4 in females ( Figure 2 ). In contrast to our observation, no gender wise variation was reported in HCV genotypes distribution in Algeria ( 17 ). However, in Libya, HCV genotype 1 was frequently found in males, whereas genotype 4 was frequently found in females ( 16 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, it was observed that the predominant genotypes in males were 1b, 1c, 3a, 3b, 5a and 6a versus 1a, 2a, 2b and 4 in females ( Figure 2 ). In contrast to our observation, no gender wise variation was reported in HCV genotypes distribution in Algeria ( 17 ). However, in Libya, HCV genotype 1 was frequently found in males, whereas genotype 4 was frequently found in females ( 16 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, our sample shows a clear predominance of subgenotype 1b (89%) followed by other types of subgenotypes. These results are in agreement with those of Debbeche et al (2013); Hmida et al (1995) and Rouabhia et al (2013) [16][17][18].…”
Section: Discussionsupporting
confidence: 93%
“…Our results were also similar to our neighboring country like India and in far away Asian country like Nepal and confirmed that most prevalent circulating in these countries was type 3a [ 41 ] but dissimilar to Americas, Europe and Japan where 1 and 2 are commonly circulating genotypes [ 42 ]. In North Africa and Middle East genotype 4 is prevalent while in Hong Kong and South Africa 5 and 6 genotypes were present [ 14 ].…”
Section: Discussionsupporting
confidence: 88%